Light activated synthesis of the atomically precise fluorescent silver cluster Ag18(Capt)14. Issue 43 (29th October 2019) - Ramsay, Hannah S.; Silverman, Max M.; Simon, David; Oleschuk, Richard D.; Stamplecoskie, Kevin G.
Abstract : A photochemical synthetic route has been tuned to direct the growth of the atomically precise fluorescent silver cluster, Ag18 (Capt)14. Abstract : Metal clusters of gold and silver with highly tunable optical and electronic properties are attractive candidates for next generation medical imaging and therapy. Of these two most commonly studied metals, silver clusters often exhibit superior optical properties ( i.e. stronger absorbance and higher emission quantum yield). The atomically precise synthesis of these clusters is essential before their use in biological applications can be realized. However, most cluster synthetic routes result in complex mixtures, where isolation and/or characterization can become incredibly challenging. Using photochemistry, we demonstrate a synthetic route for silver thiolate clusters resulting in the isolation of a pure eighteen-atom silver cluster capped by fourteen captopril ligands, Ag18 (Capt)14 . The facile control over the reduction of Ag(i ) salt that this photochemical route affords can be readily applied as a general synthesis for isolating other new, atomically precise clusters.